Peran Dukun Pandita Pada Ritual Kasada Umat Hindu di Tengger Jawa Timur - Komang Agus Darmayoga Kantina; I Gusti Ngurah Agung Yudha Pramiswara; Putu Mardika; Roni Han Wasisto (Jurnal Penelitian Agama Hindu, 2026)
The Yadnya Kasada ritual is a religio-cultural tradition of the Tengger Hindu community that has endured despite modernization, cultural commodification, and the growth of tourism. Previous studies on Yadnya Kasada have primarily focused on its ritual symbolism and cosmological dimensions, while limited attention has been given to the role of the Dukun Pandita as a social actor in the reproduction of religious and cultural authority. This study aims to analyze the role of the Dukun Pandita and their cultural practices in the Yadnya Kasada ritual through the perspective of Pierre Bourdieu’s Theory of Social Practice. The research employed a qualitative method with a descriptive-narrative approach. Data were collected through participant observation, in-depth interviews, and documentation involving Dukun Pandita, traditional leaders, religious leaders, village elders, and members of the Tengger community selected through purposive sampling. Data were analyzed interactively through data reduction, data display, and conclusion drawing, with triangulation applied to ensure data validity. The findings reveal that the Dukun Pandita serves as a ritual leader, spiritual mediator, guardian of tradition, agent of cultural reproduction, and promoter of social cohesion within the Tengger community. These practices are shaped through the interaction of habitus, cultural capital, social capital, symbolic capital, and the religious field, resulting in religious legitimacy grounded in community recognition rather than formal authority or economic capital. The Yadnya Kasada ritual also functions as a mechanism for reproducing cultural identity and as a space for negotiating between local traditions and modernity. This study concludes that the Dukun Pandita is a strategic actor in sustaining the Kasada tradition through the reproduction of symbolic authority and the intergenerational transmission of sacred knowledge. These findings contribute to the sociology of religion and culture by affirming the Dukun Pandita as an agent of social practice in preserving the cultural identity of the Tengger community.